2016
DOI: 10.1177/0888406416637411
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of an Online Graduate Program in Special Education for Emotional and Behavioral Disorders

Abstract: The purpose of this study was to evaluate graduate students' perceptions of a completely online master's degree program in special education for emotional and behavioral disorders. The Community of Inquiry survey was used to examine graduate students' perceptions of the online program in the areas of teaching, cognitive, and social presences. The results suggest that teaching and cognitive presence can be addressed with a high level of satisfaction in an online program. Activities related to creating a social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The contrasting positions reflected in the small body of extant literature on nGSEs (e.g., Caillier & Riordan, 2009;Kronholz, 2012;Zeichner, 2016) underscored the need for independent empirical studies based on access to participants, materials, and program structures. In addition, existing empirical research on fully online teacher preparation (e.g., Faulk & King, 2013;Leader-Janssen, Nordness, Swain, & Hagaman, 2016;Stricklin & Tingle, 2016) suggested that as the field of initial teacher education continues to evolve beyond the time and distance constraints of face-to-face preparation programs, the ongoing exploration of the impact of digital technologies on preparation programs remains important. Finally, research on the use of synchronous online classes in higher education (e.g., Malczyk, 2018;McDaniels, Pfund, & Bamicle, 2016;Wagner, Enders, Pirie, & Thomas, 2016) offered guidance related to the benefits and challenges of a major component of TEACH-NOW's program -its use of real-time virtual classes.…”
Section: Related Literaturementioning
confidence: 99%
“…The contrasting positions reflected in the small body of extant literature on nGSEs (e.g., Caillier & Riordan, 2009;Kronholz, 2012;Zeichner, 2016) underscored the need for independent empirical studies based on access to participants, materials, and program structures. In addition, existing empirical research on fully online teacher preparation (e.g., Faulk & King, 2013;Leader-Janssen, Nordness, Swain, & Hagaman, 2016;Stricklin & Tingle, 2016) suggested that as the field of initial teacher education continues to evolve beyond the time and distance constraints of face-to-face preparation programs, the ongoing exploration of the impact of digital technologies on preparation programs remains important. Finally, research on the use of synchronous online classes in higher education (e.g., Malczyk, 2018;McDaniels, Pfund, & Bamicle, 2016;Wagner, Enders, Pirie, & Thomas, 2016) offered guidance related to the benefits and challenges of a major component of TEACH-NOW's program -its use of real-time virtual classes.…”
Section: Related Literaturementioning
confidence: 99%